2019
DOI: 10.1002/anie.201905729
|View full text |Cite
|
Sign up to set email alerts
|

Fluorographdiyne: A Metal‐Free Catalyst for Applications in Water Reduction and Oxidation

Abstract: Ah ighly efficient bifunctional metal-free catalyst was prepared by growth of three-dimensional porous fluorographdiyne networks on carbon cloth (p-FGDY/CC). Our experiments and density functional theory (DFT) calculations show the 3D p-FGDY/CC network is highly active and it is ahigh potential metal-free catalyst for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), as well as overall water splitting (OWS) under both acidic and alkaline conditions.The experimental and theoretical resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 57 publications
0
91
1
Order By: Relevance
“…Even so, we summarize the best performance for various reactions catalyzed by different heteroatoms‐doped carbons in Figure for easy comparison. [ 118–158 ] As can be seen, N‐doped carbon catalysts show better catalytic performance over other heteroatom‐doped carbons for ORR and water splitting. For non‐N‐doping, only B‐doping has been reported for ORR, P‐doping for OER, and F‐doping for HER to show catalytic performance comparable to the N‐doping.…”
Section: Conclusion and Outlooksmentioning
confidence: 98%
“…Even so, we summarize the best performance for various reactions catalyzed by different heteroatoms‐doped carbons in Figure for easy comparison. [ 118–158 ] As can be seen, N‐doped carbon catalysts show better catalytic performance over other heteroatom‐doped carbons for ORR and water splitting. For non‐N‐doping, only B‐doping has been reported for ORR, P‐doping for OER, and F‐doping for HER to show catalytic performance comparable to the N‐doping.…”
Section: Conclusion and Outlooksmentioning
confidence: 98%
“…The porous Ni 3 FeN used as both anode and cathode in two-electrode system for overall water splitting in 1.0 M KOH required a voltage of 1.495 V at 10 mA cm −2 , which could be driven by a battery with rated voltage of 1.5 V [ 50 ]. Metal-free electrocatalysts also show high activity, good stability and low cost to replace metal-based electrocatalysts for long-term water splitting [ 54 , 55 ]. Yu, Chen, Dai et al reported a novel metal-free bifunctional electrocatalyst with the ultrathin exfoliated black phosphorus (EBP) nanosheets on N-doped graphene (EBP@NG).…”
Section: Two-electrode Electrolysis Of Watermentioning
confidence: 99%
“…Interestingly, GDY shows stacking (AA, AB and ABC stacking) dependent physical properties in the case of multilayers. 40 Aerwards, this motivated extensive studies on potential applications in water remediation, electronic devices, gas separation, Li-battery storage, metal free catalysis, 41,42 sensors and solar cell devices. 43,44 Unlike graphene, graphdiyne can be considered a promising material, particularly in spintronics.…”
Section: Reduced Graphene Oxidementioning
confidence: 99%